MEMBANGUN PERILAKU PRO-LINGKUNGAN WISATAWAN GEN Z UNTUK PARIWISATA BERKELANJUTAN - Ni Kadek Winda Yanti; Faluti, M. Zacky; Putri Gayatri, Ni Nyoman; Sri Wisudawati, Ni Nyoman (Jurnal Sains Terapan Pariwisata, 2025)
This study aims to further explore the environmentally friendly behavior of the generation Z tourist group to support the implementation of sustainable tourism. This is motivated by the dominance of tourists from this group in destinations, so that they have the potential to become agents in the formation of more environmentally friendly tourism, especially in the environmental sector. This is also supported by the tendency of this group's high adoption of social media which can encourage the creation of more targeted behavior through the user generated content method. This study uses quantitative data obtained through the distribution of questionnaires to 180 valid respondents. The number of samples itself is determined using the rule of thumb method, namely the highest number of reflective variables multiplied by 10. Respondents themselves are selected purposively with criteria such as tourism history, duration of travel and others. The data collected is then measured using SEM-PLS to assess outer loading, AVE, cronbach's alpha. This study found that generation Z tourists through UGC show a good commitment to behaving in an environmentally friendly manner and are implemented in real terms, but still need further support so that they can be implemented sustainably.